2010
DOI: 10.1177/0022466910362773
|View full text |Cite
|
Sign up to set email alerts
|

School-Age Prework Experiences of Young People With a History of Specific Language Impairment

Abstract: Young people with specific language impairment (SLI) are at risk for poorer outcomes with respect to employment in adulthood, yet little is known of how early school-age prework experiences prepare them for the job market. This study examined whether young people with SLI engage in similar types of early work experiences as their typically developing (TD) peers. A total of 139 young people with a history of SLI and 124 TD peers attending their final year of compulsory secondary education were interviewed about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…As young people approach the workforce and are guided into short‐term work placements as part of the latter years of compulsory education, adolescents with DLD are more likely to be placed in lower skilled, elementary jobs (e.g., general supermarket assistant), while their peers without a history of language problems are more likely to be placed in employment that has greater potential for skills development (e.g., classroom assistant; Durkin et al . ). Some evidence points to poor employment outcomes in early adulthood compared with peers without DLD.…”
Section: Introductionmentioning
confidence: 97%
“…As young people approach the workforce and are guided into short‐term work placements as part of the latter years of compulsory education, adolescents with DLD are more likely to be placed in lower skilled, elementary jobs (e.g., general supermarket assistant), while their peers without a history of language problems are more likely to be placed in employment that has greater potential for skills development (e.g., classroom assistant; Durkin et al . ). Some evidence points to poor employment outcomes in early adulthood compared with peers without DLD.…”
Section: Introductionmentioning
confidence: 97%
“…Identifying potential relative strengths feeds into related ways of supporting young people with this condition, including career guidance and early work placements; areas in which individuals with SLI tend to be under-served at present (Beitchman and Brownlie 2013 , Conti-Ramsden and Durkin 2012 , Durkin et al . 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The situation for young people with SEN/disabilities, and particularly for learners with SLD, is rather different. Research shows that young people with disabilities have lower rates of employment than the rest of the population (Durkin, Fraser, & Conti-Ramsden, 2012;DWP, 2011;OfSTED, 2011). In addition, although many people with learning difficulties aspire to having a job, opportunities for achieving paid employment are particularly scarce (Lundy, Bryne, & McKeown, 2012).…”
Section: Purposes Of Education For Learners With Sldmentioning
confidence: 99%
“…A national indicator report (HSCIC, 2012) found that only 6.6% of adults with moderate to severe learning difficulties known to social services were in paid employment at the time and another report noted that 79% of people with severe learning disabilities have never worked (DWP, 2013). Durkin et al (2012) acknowledge that, over the past few decades in the UK, professionals, policy-makers and researchers have sought to improve transition from school to employment for young people with disabilities. They add, however, that experiences and outcomes vary according to nature of disability and need and that research and policy often neglects to explore provision for young people with learning difficulties.…”
Section: Purposes Of Education For Learners With Sldmentioning
confidence: 99%